Assessing Survival and Grading the Severity of Complications in Octogenarians Undergoing Pulmonary Lobectomy - Feczko, Andrew (Can Respir J, 2017)
Introduction. Octogenarians are at increased risk for complications after lung resection. With alternatives such as radiation, understanding the risks of surgery and associated survival are valuable. Data grading the severity of complications and long-term survival in this population is lacking. We reviewed our experience with lobectomy in octogenarians, grading complications using a validated thoracic morbidity and mortality schema. Methods. We retrospectively reviewed consecutive patients aged ≥80 undergoing lobectomy between 2004 and 2012. Demographics, clinical/pathologic stage, complications, recurrence, and mortality were collected. Complications were graded by the Seely thoracic morbidity and mortality model. Results. 45 patients (mean age 82.2 years) were analyzed. The majority of patients (28/45, 62%) were clinical stage IA/IB. 62% (28/45) of patients experienced a complication. Only 15.6% (7/45) were considered significantly morbid (≥ grade IIIB) per the Seely model. Perioperative mortality was 2% and half of patients were living at a follow-up of 53 months. Overall five-year survival was 52%. Conclusions. In carefully selected octogenarians, lobectomy carries a 15.6% rate of significantly morbid complications with encouraging overall survival. These data provide the basis for a more complete discussion with patients regarding lobectomy for lung cancer.